Pengaruh Rasio Utang Terhadap Ekuitas, Rasio Likuiditas Jangka Pendek, Rasio Laba atas Aset Serta Dampaknya Terhadap Nilai Saham PT Semen Indonesia (Persero) Tbk (2007-2023) - Kezia, josephin (Asosiasi Dosen Akuntansi Indonesia, 2024)
This study aims to evaluate the effect of Debt to Equity Ratio (DER), Current Ratio (CR), and Return on Assets (ROA) on the stock price movement of PT Semen Indonesia (Persero) Tbk during the period 2007-2023. The data used comes from the company's annual financial report and stock movements published by the Indonesia Stock Exchange (IDX). This study uses multiple linear regression analysis to test the relationship between these financial ratios and stock price movements. The results of the study show that although the DER ratio has decreased significantly, stock prices do not always move up, indicating that external factors such as industry and market conditions have a greater influence on stock movements. In addition, high CR indicates strong company liquidity but does not always reflect efficient use of assets. A consistently decreasing ROA also indicates a decrease in the company's efficiency in utilizing assets to generate profits, which affects investor perceptions